Total ankle arthroplasty (TAA) in a hemophiliac patient: case report - Silva, João Luiz Viera da; Pacheco, Luciano Rocha Loures; Nakahashi, Eiji Rafael; Picini, Marcos (Scientific Journal of the Foot & Ankle, 2018)
Hemophilia is a genetically inherited disease linked to the X chromosome. The main alteration of this pathology affects the coagulation mechanisms. The most affected joints are the knees, elbows and ankles. Clinical manifestations include pain, joint bleeding and limited movement. The diagnosis takes into account the clinical picture and imaging tests. In this article, we present the case of a patient with restricted performance of activities of daily living and loss of quality of life due to hemophilic arthropathy in the right ankle. After total joint arthroplasty of the affected joint, there was improvement in the preoperative parameters of the patient. Level of Evidence V; Expert Opinion.